Performance Measure Congruity and the Balanced Scorecard - BUDDE, JÖRG (Journal of Accounting Research, 2007)
ABSTRACT This paper studies the incentive effects of a balanced scorecard within a multitask agency framework under both formal and relational contracts. First, the main characteristics of the balanced scorecard are analyzed with respect to performance measure congruity. It is shown that under complete verifiability, a properly designed balanced scorecard is capable of perfectly aligning the interests of owners and employees by means of an explicit contract. I then investigate whether subjective performance evaluation is beneficial when not all the scorecard measures are contractible. It emerges that congruity of the contractible scorecard measures constrains a purely implicit incentive contract, but the first‐best solution may still be obtained through a combination of formal and relational contracts. Furthermore, a purely explicit contract in most cases can be improved by incorporating subjective rewards.